2021
DOI: 10.3390/catal11020240
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Advanced Oxidation Processes for the Degradation of Maprotiline in Water—Kinetics, Degradation Products and Potential Ecotoxicity

Abstract: The impact of different oxidation processes on the maprotiline degradation pathways was investigated by liquid chromatography-high resolution mass spectrometry (LC/HRMS) experiments. The in-house SPIX software was used to process HRMS data allowing to ensure the potential singular species formed. Semiconductors photocatalysts, namely Fe-ZnO, Ce-ZnO and TiO2, proved to be more efficient than heterogeneous photo-Fenton processes in the presence of hydrogen peroxide and persulfate. No significant differences were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Maprotiline (MPT) can be regarded as either a TCA or tetracyclic antidepressant (TeCA), and it has been shown to be unstable under doubled ICH conditions (400 W m −2 and 2.4 × 10 6 lx h) [2]. Liquid chromatography-high resolution mass spectrometry (LC/HRMS) (Acquity HPLC system, Water Technologies, Guyancourt, France, coupled with a Bruker SolarixXR FT-ICR 9.4 T MS instrument, Bruker Daltonics, Bremen, Germany) showed that MPT degradation using semiconductor photocatalysts (Fe-ZnO, Ce-ZnO, TiO 2 ) was more efficient than heterogeneous photo-Fenton processes (H 2 O 2 , persulfate) [102]. Significant bioaccumulation (170 µg/kg) of MPT was observed in blue mussels with the formation of 12 intermediates resulting from hydroxylation/oxidation and ring opening [102].…”
Section: Degradation Of Amitriptyline: Parameters Products and Kineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Maprotiline (MPT) can be regarded as either a TCA or tetracyclic antidepressant (TeCA), and it has been shown to be unstable under doubled ICH conditions (400 W m −2 and 2.4 × 10 6 lx h) [2]. Liquid chromatography-high resolution mass spectrometry (LC/HRMS) (Acquity HPLC system, Water Technologies, Guyancourt, France, coupled with a Bruker SolarixXR FT-ICR 9.4 T MS instrument, Bruker Daltonics, Bremen, Germany) showed that MPT degradation using semiconductor photocatalysts (Fe-ZnO, Ce-ZnO, TiO 2 ) was more efficient than heterogeneous photo-Fenton processes (H 2 O 2 , persulfate) [102]. Significant bioaccumulation (170 µg/kg) of MPT was observed in blue mussels with the formation of 12 intermediates resulting from hydroxylation/oxidation and ring opening [102].…”
Section: Degradation Of Amitriptyline: Parameters Products and Kineticsmentioning
confidence: 99%
“…Liquid chromatography-high resolution mass spectrometry (LC/HRMS) (Acquity HPLC system, Water Technologies, Guyancourt, France, coupled with a Bruker SolarixXR FT-ICR 9.4 T MS instrument, Bruker Daltonics, Bremen, Germany) showed that MPT degradation using semiconductor photocatalysts (Fe-ZnO, Ce-ZnO, TiO 2 ) was more efficient than heterogeneous photo-Fenton processes (H 2 O 2 , persulfate) [102]. Significant bioaccumulation (170 µg/kg) of MPT was observed in blue mussels with the formation of 12 intermediates resulting from hydroxylation/oxidation and ring opening [102]. Nortriptyline was detected as an effluent from WWTPs (wastewater treatment plants) in concentrations of about 13 ng/L [2] or 66 (effluents)-2092 ng/L (influents, UK) [6].…”
Section: Degradation Of Amitriptyline: Parameters Products and Kineticsmentioning
confidence: 99%
“…All these physicochemical properties were studied only for a number of ecotoxicants, since some substances are either extremely difficult to separate in pure form, or they have not yet been synthesized. There are a large number of isomers and homologues for ecotoxicants, which are also toxic [5,6]. An urgent problem is the development of methods for predicting the physicochemical properties of individual compounds based on their presumed structure.…”
mentioning
confidence: 99%
“…In another contribution [15], Gonçalves et al investigated the impact of different oxidation processes on the maprotiline degradation pathways via liquid chromatography-highresolution mass spectrometry (LC/HRMS) experiments. Semiconductors photocatalysts-namely, Fe-ZnO, Ce-ZnO, and TiO 2 -proved to be more efficient than heterogeneous photo-Fenton processes in the presence of hydrogen peroxide and persulfate.…”
mentioning
confidence: 99%